Transient viral exposure drives functionally-coordinated humoral immune responses in HIV-1 post-treatment controllers - Luis M. Molinos-Albert; Valérie Lorin; Valérie Monceaux; Sylvie Orr; Asma Essat; Jérémy Dufloo; Olivier Schwartz; Christine Rouzioux; Laurence Meyer; Laurent Hocqueloux; Asier Sáez-Cirión; Hugo Mouquet; et al. (Nature Communications, 2022)
A rare sub-population of people living with HIV-1 experience long-lasting viral remission after interrupting antiretroviral therapy and are considered post-treatment controllers. Here the authors characterise the humoral immune response to HIV-1 in a cohort of post-treatment controllers.